Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Certainly! Let's break down the problem step-by-step.
We're given two functions:
[tex]\( f(x) = 2x^2 + 3 \)[/tex]
[tex]\( g(x) = x^2 - 7 \)[/tex]
To find the value of these functions at a specific point, we need to choose a value for [tex]\( x \)[/tex]. Let's use [tex]\( x = 1 \)[/tex].
### Let's evaluate [tex]\( f(x) \)[/tex] for [tex]\( x = 1 \)[/tex]:
1. Start by substituting [tex]\( x = 1 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(1) = 2(1)^2 + 3 \][/tex]
2. Calculate the square of 1:
[tex]\[ 1^2 = 1 \][/tex]
3. Multiply the result by 2:
[tex]\[ 2 \times 1 = 2 \][/tex]
4. Add 3 to the result:
[tex]\[ 2 + 3 = 5 \][/tex]
So, [tex]\( f(1) = 5 \)[/tex].
### Now, let's evaluate [tex]\( g(x) \)[/tex] for [tex]\( x = 1 \)[/tex]:
1. Substitute [tex]\( x = 1 \)[/tex] into the function [tex]\( g(x) \)[/tex]:
[tex]\[ g(1) = (1)^2 - 7 \][/tex]
2. Calculate the square of 1:
[tex]\[ 1^2 = 1 \][/tex]
3. Subtract 7 from the result:
[tex]\[ 1 - 7 = -6 \][/tex]
So, [tex]\( g(1) = -6 \)[/tex].
### Final Answer:
For [tex]\( x = 1 \)[/tex]:
- [tex]\( f(1) = 5 \)[/tex]
- [tex]\( g(1) = -6 \)[/tex]
So the results are [tex]\( (5, -6) \)[/tex].
We're given two functions:
[tex]\( f(x) = 2x^2 + 3 \)[/tex]
[tex]\( g(x) = x^2 - 7 \)[/tex]
To find the value of these functions at a specific point, we need to choose a value for [tex]\( x \)[/tex]. Let's use [tex]\( x = 1 \)[/tex].
### Let's evaluate [tex]\( f(x) \)[/tex] for [tex]\( x = 1 \)[/tex]:
1. Start by substituting [tex]\( x = 1 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(1) = 2(1)^2 + 3 \][/tex]
2. Calculate the square of 1:
[tex]\[ 1^2 = 1 \][/tex]
3. Multiply the result by 2:
[tex]\[ 2 \times 1 = 2 \][/tex]
4. Add 3 to the result:
[tex]\[ 2 + 3 = 5 \][/tex]
So, [tex]\( f(1) = 5 \)[/tex].
### Now, let's evaluate [tex]\( g(x) \)[/tex] for [tex]\( x = 1 \)[/tex]:
1. Substitute [tex]\( x = 1 \)[/tex] into the function [tex]\( g(x) \)[/tex]:
[tex]\[ g(1) = (1)^2 - 7 \][/tex]
2. Calculate the square of 1:
[tex]\[ 1^2 = 1 \][/tex]
3. Subtract 7 from the result:
[tex]\[ 1 - 7 = -6 \][/tex]
So, [tex]\( g(1) = -6 \)[/tex].
### Final Answer:
For [tex]\( x = 1 \)[/tex]:
- [tex]\( f(1) = 5 \)[/tex]
- [tex]\( g(1) = -6 \)[/tex]
So the results are [tex]\( (5, -6) \)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.